2002
DOI: 10.1111/j.1530-0277.2002.tb02542.x
|View full text |Cite
|
Sign up to set email alerts
|

CDT, GGT, and AST As Markers of Alcohol Use: The WHO/ISBRA Collaborative Project

Abstract: CDT was little better than GGT in detecting high- or intermediate-risk alcohol consumption in this large, multicenter, predominantly community-based sample. As the two tests are relatively independent of each other, their combination is likely to provide better performance than either test alone. Test interpretation should take account sex, age, and body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(101 citation statements)
references
References 27 publications
4
94
0
1
Order By: Relevance
“…This gender variation has been recently demonstrated for %CDT (5,39 ) and agrees with the most recent WHO/ISBRA assessment that CDT is a slightly but significantly better marker of high-risk consumption in men (40 ). Turpeinen et al (27 ) recently reported a 1.8% cutoff for HPLC analysis of disialo-Tf.…”
Section: Discussionsupporting
confidence: 61%
“…This gender variation has been recently demonstrated for %CDT (5,39 ) and agrees with the most recent WHO/ISBRA assessment that CDT is a slightly but significantly better marker of high-risk consumption in men (40 ). Turpeinen et al (27 ) recently reported a 1.8% cutoff for HPLC analysis of disialo-Tf.…”
Section: Discussionsupporting
confidence: 61%
“…A couple of markers such as -glutamyltransferase (GGT) or carbohydrate deficient transferrin (CDT) may be the most appropriate for the early detection of nondependent hazardous or harmful drinking (Sillanaukee et al 2000;Conigrave et al 2002), inasmuch as the elevated GGT or CDT is not always indicative of a clinically diagnosed disease. Aspartate aminotransferase (AST) seems to be a primary marker for hepatocellular injury (Stewart 2002), because it is more specific than other liver enzymes for detecting alcohol-induced hepatocyte necrosis (Cohen and Kaplan 1979).…”
mentioning
confidence: 99%
“…CDT is more specific than GGT. [48][49][50] Ethyl glucuronide is a direct metabolite of alcohol and it can be measured in tissues, blood, hair, and urine. 42 Urinary ethyl glucuronide offers several advantages over other biomarkers of alcohol relapse.…”
Section: How To Assess Relapse After Liver Transplantmentioning
confidence: 99%